Dreams And Hope Of A Popcorn Seller Reflected In Max Giwa's Street Dance Movie (2012): An Individual Psychological Approach - Kurniawati, Anny; , Dr. Phil. Dewi Candraningrum, S.Pd., M.Ed.; , Titis Setyabudi, S.S., M.Hum (2013)
In this study, researcher discussed the dream of Falk Hentschel as the main character in the Street Dance film. The purpose of this study is: to analyze a dream in the Street Dance film based on the structural elements and individual psychological approach. This research is qualitative research. There are two types of data, namely primary and secondary data. The primary data source comes from the Street Dance film and secondary data from books, internet, or information related to the research. Then, the data were analyzed based on individual psychological theory proposed by Alfred Adler. In analyzing the data, the researcher used a descriptive analysis. The conclusion is based on individual psychological analysis. It focuses on Falk Hentschel as the main character which is reflected in feelings of inferiority and compensation, energetic, strive for excellence, social interests, lifestyles, and strong determination of the self.